The Role of Pharmacists in Supporting the Stunting Program in Tulungagung Regency - Alam Qurori, Kordio; Adi Wibisono; Janik Kurniawati; Fidi Setyawan (Universitas STRADA Indonesia, 2025)
Stunting remains a health problem that threatens the quality of life for future generations. Pharmacists have the potential to play a strategic role in supporting stunting prevention programs. This study aims to explain the role of pharmacists in supporting stunting prevention programs in Tulungagung. The research method used was descriptive observational with qualitative and quantitative approaches through a cross-sectional design. Data collection was conducted using a questionnaire using a total sampling technique from pharmacists and stakeholders related to the idiom 7 pharmacies and community health centers. The results showed that stakeholders had high motivation and positive perceptions of the teaching program. Statistical analysis proved opinions about program (p=0.003) and pharmacist motivation (p=0.007) had a significant influence on the success of implementation. It was concluded that pharmacists have an important role in education, supplementation, and early detection, but optimizing this role requires strengthening systems, training, and policies that support cross-sector collaboration.